Relationship Between Attitude and Knowledge of the Behavior of Scabies Patients at PKU Muhammadiyah Delanggu Hospital - Hartini, Melok Tin; Purnamasari, Rina; Indrastiti, Retno; Ma'mun Sukri, Muhamad; Atthariq Ilmi, Putri (Ahmad Dahlan Medical Journal, 2024)
Scabies is a skin condition caused by Sarcoptes scabiei variant hominis infestation. Scabies risk factors include a person's education and attitude toward personal and environmental hygiene. This study aims to investigate the relationship between attitudes and knowledge of the behavior of scabies patients at PKU Muhammadiyah Delanggu Hospital. This is a cross-sectional analytic study. The participants in this study were scabies patients who examined themselves at PKU Muhammadiyah Delanggu Klaten Hospital between January and September 2023. The sequential sampling method was used to obtain a sample of 135 subjects. The Fisher exact test is used to analyze univariate and bivariate data. The majority of scabies patients were aged 10-19 years (30.4%), whereas the minority were aged 30-39 years (3.0%). Men 57.8% are more than women 42.2%. The majority of scabies diagnoses (68.1%) were obtained through auto anamnesis, and approximately half of the patients (50.4%) possessed three of the four cardinal symptoms used for scabies diagnosis. With a p-value of 0.546 (p>0.05), the Fisher exact test demonstrates that knowledge is not related to a patient's behavior. However, the attitude factors test showed a p-value of less than 0.001, indicating that attitudes affect how scabies patients behave at the PKU Muhammadiyah Delanggu Hospital's Dermatology and Venereology clinic in Klaten. The results of the research show that there was a significant relationship between attitudes, rather than knowledge, significantly predicting how scabies patients behave in the Dermatology & Venereology clinic of PKU Muhammadiyah Delanggu Hospital, Klaten.